2017
DOI: 10.11124/jbisrir-2017-003363
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test accuracy of self-reported frailty screening instruments in identifying community-dwelling older people at risk of frailty and pre-frailty: a systematic review protocol

Abstract: The question of this systematic review is: What is the diagnostic test accuracy of self-reported frailty screening instruments among community-dwelling older people against any of the following reference standard tests: the frailty phenotype, frailty index and comprehensive geriatric assessment?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Self-administered instruments show potential as one means of offering greater efficiency within general practice settings, although their diagnostic accuracy and feasibility have not been well determined to date [46]. Time to complete was not collected for the two selfadministered instruments assessed within this study (KC and REFS).…”
Section: Discussionmentioning
confidence: 99%
“…Self-administered instruments show potential as one means of offering greater efficiency within general practice settings, although their diagnostic accuracy and feasibility have not been well determined to date [46]. Time to complete was not collected for the two selfadministered instruments assessed within this study (KC and REFS).…”
Section: Discussionmentioning
confidence: 99%
“…Do self-reported frailty to predict survival in adults with bacterial meningitis screening instruments (index test) accurately identify older people (population) at risk of frailty and prefrailty (condition of interest)? 10 Is PET 18F florbetapen (index test) useful in early diagnosing dementia (condition) in patients with mild cognitive impairment (population)? 11…”
Section: Pird-s (Population Index Test Reference Test Diagnosis Ofmentioning
confidence: 99%
“…The resources were organised in 7 sections, following the development stages of an SR: 1) Formulating the research question, 2) development of the protocol and review registration, 3) search strategy, 4) risk of bias assessment, 5) statistical synthesis of findings, 6) quality of evidence assessment, and 7) results report and presentation. The resources are presented by type of SR in each section, and an example of their use is included [5][6][7][8][9][10][11][12][13] .…”
Section: Data Selection and Extractionmentioning
confidence: 99%
“…Case-control designs are subject to risk of bias and their inclusion in diagnostic SRs is not recommended 25 . For instance, Ambagtsheer et al (2017) include in their SR cross-sectional studies where one or more self-reported frailty screening scales have been compared with one of three reference standards: frailty phenotype, frailty index or comprehensive geriatric assessment 10 .…”
Section: Diagnostic Accuracy Review Diagnosticmentioning
confidence: 99%
“…For instance, the protocol of the SR by Ambagtsheer et al (2017) expects to estimate an average sensitivity and specificity for the frailty scales, when the included studies have applied the same explicit cut-off points to the considered scales. However, given that they are subjective, self-reported scales, the studies could share the same explicit cut-off point, and yet that cut-off point could correspond to different levels of frailty in the studies (implicit thresholds), which will advise against calculating pooled estimates of diagnostic accuracy 10 .…”
Section: Diagnostic Accuracy Reviewmentioning
confidence: 99%